Peran Pendidikan dan Kesehatan dalam Mengurangi Ketimpangan dan Kemiskinan di Indonesia: Pendekatan Human Capital - Abrianti, Selsha; Suchaina, Suchaina (FEB Universitas Sultan Ageng Tirtayasa, 2025)
Human capital refers to the intellectual qualities and abilities of individuals that can be used to increase productivity. The theory of human capital, put forward by Gery Becker, explains that investment in education and health can increase individual productivity, thereby driving economic growth. Education and welfare are interrelated, where good health can support a quality learning process and good education can encourage better health. The literature study method was chosen to analyze the role of education and health in reducing inequality and poverty in Indonesia with a focus on the perspective of human capital. The use of secondary data in this study is used to test existing empirical evidence and theories, so that it can provide an in-depth understanding of the role of education and health in developing quality human resources. Increasing public awareness of the importance of primary and secondary education also faces challenges related to gaps in access to education services between urban and rural areas and between provinces, which also have an impact on differences in health outcomes. The government supports human resource development through the Program Indonesia Pintar (PIP) and the Jaminan Kesehatan Nasional (JKN) to improve education and health.